2021
DOI: 10.5194/tc-2021-287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverting ice surface elevation and velocity for bed topography and slipperiness beneath Thwaites Glacier

Abstract: Abstract. There is significant uncertainty over how ice sheets and glaciers will respond to rising global temperatures. Limited knowledge of the topography and rheology of ice-bed interface is a key cause of this uncertainty, as models show that small changes in the bed can have a large influence on predicted rates of ice loss. Most of our detailed knowledge of bed topography comes from airborne and ground-penetrating radar observations. However, these direct observations are not spaced closely enough to meet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…This relation is qualitatively consistent with that predicted from linearized small-perturbation theory for bed-tosurface transfer (Gudmundsson, 2003;Ng et al, 2018), that is, subglacial topographic perturbations that are sufficiently wide along-flow relative to local ice thickness commonly induce detectable surface expressions. That linearized theory is potentially exploitable to resolve subglacial topography at finer resolution (Ockenden et al, 2022(Ockenden et al, , 2023, but more physically complete modeling has demonstrated that three-dimensional effects and non-linear ice rheology further complicate its interpretation (e.g., Sergienko, 2012). Regardless, it is clear that numerous subglacial topographic features across the GrIS interior-primarily subglacial valleys-are poorly resolved by existing surveys and interpolations.…”
Section: Discussionmentioning
confidence: 99%
“…This relation is qualitatively consistent with that predicted from linearized small-perturbation theory for bed-tosurface transfer (Gudmundsson, 2003;Ng et al, 2018), that is, subglacial topographic perturbations that are sufficiently wide along-flow relative to local ice thickness commonly induce detectable surface expressions. That linearized theory is potentially exploitable to resolve subglacial topography at finer resolution (Ockenden et al, 2022(Ockenden et al, , 2023, but more physically complete modeling has demonstrated that three-dimensional effects and non-linear ice rheology further complicate its interpretation (e.g., Sergienko, 2012). Regardless, it is clear that numerous subglacial topographic features across the GrIS interior-primarily subglacial valleys-are poorly resolved by existing surveys and interpolations.…”
Section: Discussionmentioning
confidence: 99%
“…2b). Features oriented perpendicular to flow are more likely to be transmitted to the surface, because they present a greater obstacle to flow than those oriented parallel (Ockenden et al, 2021).…”
Section: Morphometrymentioning
confidence: 99%
“…8), present insufficient obstacle to cause an expression visible on the ice surface (c.f. Ockenden et al, 2021). Since there is diversity in the orientations of LC features, it may be reasonably supposed that those that lie at greater angles to the direction of ice surface flow are more likely to represent glacial breaches.…”
Section: Landscape Evolutionmentioning
confidence: 99%